THE COVID-19 IMPACT ON GLOBAL POLICE RESPONSE IN RELATION TO ONLINE CHILD SEXUAL EXPLOITATION AND ABUSE (Годишен зборник на Филозофски факултет - Скопје, 2023)
In this paper we draw attention that there have been significant increases in activity relating to child sexual abuse and exploitation on both the surface web and dark web during the COVID-19 lockdown period. This paper aim is an analyse about how the COVID-19 pandemic is presently modifying the trends and threats of child sexual exploitation and abuse offences, which were already at high levels prior to the pandemic. This article highlights the trends and threats in the current COVID-19 context compared to pre-pandemic measures, what impact these are having in the short-term, and what changes we have seen when COVID-19 measures are reduced. It contributes to the space of the dark web during lockdown by manifestation on the ongoing organised business model that has evolved as technology expands and the level of threat that it poses to children. The objective is to share these trends across the global law enforcement community and science in order to improve the monitoring and detection of child sexual exploitation and abuse online, further investigations and global police response.